Significant Nutritional Gaps in Tibetan Adults Living in Agricultural Counties Along Yarlung Zangbo River - Zhou, Chen-ni; Li, Mo; Xiao, Ran; Zhao, Fang-jie; Zhang, Fu-suo (Frontiers in Nutrition, 2022)
Background: Dietary intake and nutritional assessing data from a representative sample of adult population living in an agricultural zone on Tibet Plateau are still lacking nowadays. This study aimed to assess the daily dietary intakes and respective food sources in 552 local residents (≥ 18 years old, 277 men and 275 women) living in 14 agricultural counties along the Yarlung Zangbo River on Tibet Plateau. Methods: Food consumption data and dietary and 18 nutrient intakes were collected using a 2-day, non-consecutive 24 h recall combined with a validated cultural-specific food frequency questionnaire that contained all local Tibetan foods and analyzed with three fixed factors: gender, age, and region. Nutritional gaps and the percentages of participants who had inadequate and excessive nutrient intakes were calculated by estimated average requirement (EAR) cut-point methods. Results: Compared with the dietary reference intakes, 68.4% of nutrient intakes were inadequate. Fiber, Ca, I, Zn, Se, and vitamin (Va, Vc, and folic acid) intakes appeared to be particularly deficient. The dietary intakes of most nutrients were below the estimated energy requirement/EAR or adequate intake values, while more than 70% of the participants had excessive intake of carbohydrate, especially the elderly (aged ≥ 51 years). The nutritional gap of Cu was more than 300%. Almost 100% of the participants was vulnerable to fiber, Se, and Va shortfalls due to the deficiency in sole food sources. Eggs (42.1%), tubers (62.2%), vegetables (66.4%), and highland barley (49.7%) were the first contributors of Va, Ve, Vc, and folic acid, respectively. Conclusion: The dietary intake of a large sample of Tibetan adult population living in agricultural counties of Tibetan Autonomous Region is alarmingly insufficient. Gender inequality is common, and regional difference is widespread due to rapid urbanization. Young Tibetan adults aged 18–30 years are particularly vulnerable to micronutrient shortfalls and currently facing the risk of nutrition-insecurity-related dietary inadequacy. The respondents who belong to the elderly category (≥ 51 years of age) are facing the risk of “double burden of malnutrition” characterized by the coexistence of undernutrition, including micronutrient deficiencies and overweight or obesity.